Bahasa Sunda Di Jatinegara Kaum Dan Pemukiman Keturunan Pangeran Achmad Djaketra - Wati Kurniawati (Balai Arkeologi Yogyakarta, 1996)
Based on historical reviews, the speakers of Sundanese language are the descendants of Prince Achmad Djaketra and Prince Sugeri who used the title